Physical Exercise in Early Recovery in Post COVID-19 Patient: Case Study - Betancourt Peña, Jhonatan (2025)
Prolonged stays in the Intensive Care Unit (ICU) in patients with COVID-19 are associated with serious short-term sequelae including severe muscle injuries, functional impairment, limitations in exercise capacity, and poor quality of life. Early pulmonary rehabilitation as an integral component is a non-pharmacological treatment alternative in the management of pulmonary sequelae caused by COVID-19. This study aimed to describe the impact of early pulmonary rehabilitation in a case of a patient with COVID-19 sequelae. The case of a 73-year-old woman with COVID-19 sequelae who underwent early pulmonary rehabilitation is presented. In conclusion, there is evidence of an improvement in symptoms, functional/aerobic capacity and health-related quality of life.